Roles of Tick Symbiotic Microorganisms in Pathogen Transmission - Xiongxiong Chang; Xiang Li; Yaping Pei; Enjie Deng; Shubiao Wu; Jiafu Jiang; Lin Jin (Zoonoses)
Ticks have garnered significant research interest owing to their ability to vector pathogens into humans and animals. The intricate symbiotic associations between ticks and tick microbiota substantially influence developmental processes, reproductive success, and potential to serve as vectors for tick-transmitted diseases. This paper reviews the epidemiology of diseases transmitted by ticks and delves into the composition and function of tick endosymbionts in transmission and infection. This review also highlights the role of tick immunity in maintaining gut homeostasis. Finally, tick symbiont-pathogen interactions and potential strategies for controlling tick-borne diseases by leveraging symbiotic relationships are discussed.